COVID-19 and Neutrophils: The Relationship between Hyperinflammation and Neutrophil Extracellular Traps - Leandro Borges; Tania Cristina Pithon-Curi; Rui Curi; Elaine Hatanaka (Mediators of Inflammation)
Coronavirus disease 2019 (COVID-19) is a virus-induced respiratory disease that may progress to acute respiratory distress syndrome (ARDS) and is triggered by immunopathological mechanisms that cause excessive inflammation and leukocyte dysfunction. Neutrophils play a critical function in the clearance of bacteria with specific mechanisms to combat viruses. The aim of this review is to highlight the current advances in the pathways of neutrophilic inflammation against viral infection over the past ten years, focusing on the production of neutrophil extracellular traps (NETs) and its impact on severe lung diseases, such as COVID-19. We focused on studies regarding hyperinflammation, cytokine storms, neutrophil function, and viral infections. We discuss how the neutrophil’s role could influence COVID-19 symptoms in the interaction between hyperinflammation (overproduction of NETs and cytokines) and the clearance function of neutrophils to eliminate the viral infection. We also propose a more in-depth investigation into the neutrophil response mechanism targeting NETosis in the different phases of COVID-19.